2022
DOI: 10.3390/biom12070909
|View full text |Cite
|
Sign up to set email alerts
|

Rational and Translational Implications of D-Amino Acids for Treatment-Resistant Schizophrenia: From Neurobiology to the Clinics

Abstract: Schizophrenia has been conceptualized as a neurodevelopmental disorder with synaptic alterations and aberrant cortical–subcortical connections. Antipsychotics are the mainstay of schizophrenia treatment and nearly all share the common feature of dopamine D2 receptor occupancy, whereas glutamatergic abnormalities are not targeted by the presently available therapies. D-amino acids, acting as N-methyl-D-aspartate receptor (NMDAR) modulators, have emerged in the last few years as a potential augmentation strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 418 publications
0
27
0
Order By: Relevance
“…In the same experimental setting, the mGlu2/3R agonist LY379268 differentially modified the network oscillatory activity, reducing the power of high-frequency gamma bands in control Wistar but not in Han Wistar rats [ 144 ]. In addition, regulators of the NMDAR have been experimented in clinical trials and may account for beneficial antipsychotic effects also by modulating brain connectivity [ 6 ]. Specifically, SSR504734, an inhibitor of the glycine transporter-1 (GlyT1) could enhance the NMDAR-mediated glutamatergic neurotransmission by increasing extracellular glycine levels and was shown to significantly reduce the ketamine-induced increase of brain metabolic activity in the PFC, cingulate cortex, hippocampus, nucleus accumbens, and anteroventral thalamic nucleus [ 145 ].…”
Section: Antipsychotics-mediated Modulation Of Functional Connectivit...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the same experimental setting, the mGlu2/3R agonist LY379268 differentially modified the network oscillatory activity, reducing the power of high-frequency gamma bands in control Wistar but not in Han Wistar rats [ 144 ]. In addition, regulators of the NMDAR have been experimented in clinical trials and may account for beneficial antipsychotic effects also by modulating brain connectivity [ 6 ]. Specifically, SSR504734, an inhibitor of the glycine transporter-1 (GlyT1) could enhance the NMDAR-mediated glutamatergic neurotransmission by increasing extracellular glycine levels and was shown to significantly reduce the ketamine-induced increase of brain metabolic activity in the PFC, cingulate cortex, hippocampus, nucleus accumbens, and anteroventral thalamic nucleus [ 145 ].…”
Section: Antipsychotics-mediated Modulation Of Functional Connectivit...mentioning
confidence: 99%
“…Most antipsychotics, albeit with individual differences, share the common feature of occupying the dopamine D2 receptor (D2R), which is considered the main mechanism responsible for their therapeutic effect [ 3 ]. Despite the relevance of dopamine-related action, atypical antipsychotics and novel compounds in experimental trials modulate other neurotransmitter pathways, including the serotonergic, glutamatergic, and adrenergic ones with a putative beneficial effect on psychotic symptoms [ 4 , 5 , 6 ]. Mounting evidence suggests that antipsychotics can lead to morphological and synaptic changes in the brain through the modulation of processes that regulate synaptic plasticity, dendritic spine architecture, and postsynaptic density [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no cumulative evidence of significant clinically beneficial differences was shown, except for improvement in negative symptoms with memantine and minocycline [ 220 ]. It is possible that the use of additional glutamatergic agents in patients receiving clozapine may have little effect, possibly due to a putative ceiling effect on the NMDAR transmission enhancement already exerted by clozapine [ 221 ]. Strategies based on the potentiation of glutamatergic signaling by glycinergic agents (e.g., glycine and D-serine), glycine transporter 1 (GlyT1) inhibitors (e.g., bitopertin and BI 425809), and other glutamate allosteric NMDAR modulators (e.g., CNS4) have been tested.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies in an animal model of Sch have demonstrated that a decrease in the level of D-Ser in the CNS due to a decrease in SR activity can cause Sch symptoms, including stereotypy, cognitive impairment, impaired prepulse inhibition (a measure of sensorimotor gating), persistent latent inhibition (a measure of inhibition of learning and cognitive flexibility) and a lack of social interaction [ 38 , 96 , 97 ].…”
Section: D-serinementioning
confidence: 99%
“…Various studies in animal models and humans have demonstrated that D-amino acids, in particular D-Ser and D-Asp ( Table 1 ) [ 38 ], are able to modulate various NMDAR-dependent processes, including synaptic plasticity, brain development, cognition and aging brain [ 39 ]. Dysfunctional NMDAR activity is associated with the etiology and pathophysiology of a wide range of psychiatric and neurological disorders, including Sch [ 40 ].…”
Section: Introductionmentioning
confidence: 99%